Underwater Superoleophobicity: Nacre‐Inspired Mineralized Films with High Transparency and Mechanically Robust Underwater Superoleophobicity (Adv. Mater. 11/2020). Issue 11 (17th March 2020) - Chen, Wei; Zhang, Pengchao; Zang, Ruhua; Fan, Junbing; Wang, Shutao; Wang, Bailiang; Meng, Jingxin
Abstract : In article number 1907413, Shutao Wang, Bailiang Wang, Jingxin Meng, and co‐workers prepare a transparent and mechanically robust underwater superoleophobic film by combining superspreading and biomineralization. The nacre‐like composition and structures significantly improve the mechanical properties of the film, imparting a robust underwater superoleophobicity and ultralow oil‐adhesion. Such films can be coated on different transparent materials and have promising applications in areas such as underwater optics and biological imaging.